Improving quality of electricity generated by grid-tied inverters in solar power plants in low generated power mode using frequency adaptive PWM - Plakhtii, Oleksandr; Nerubatskyi, Volodymyr; Ivakhno, Volodymyr; Zamaruiev, Volodymyr (Walter de Gruyter GmbH, 2024)
The article presents the results of a study of the dependence of the quality indicators of electricity generated by solar power plants in three-phase electrical networks on the level of generated power. In the course of the study, it was established that when the generated power is reduced, the grid voltage inverters that are part of the solar power plants cause an increase in the share of higher harmonic currents to the electric grid. An analysis of international standards regarding the quality requirements of the generated current was performed, which showed that when the level of generated power decreases, the quality of electric energy decreases and may not meet the requirements of the standard. The algorithm of frequency-adaptive pulse-width modulation is proposed, which allows to improve the quality indicators of the electricity generated by the grid inverter of the voltage of the solar power plant to the electrical grid.

Die Qualitätsindikatoren des von Solarkraftwerken in dreiphasigen Stromnetzen erzeugten Stroms werden in Abhängigkeit von der Höhe der erzeugten Leistung untersucht. Es zeigt sich, dass Netzspannungswechselrichter in Solarkraftwerken bei abnehmender erzeugter Leistung zu einem Anstieg des Anteils höherer Oberschwingungsströme im Stromnetz führen. Es wird eine Analyse internationaler Qualitätsstandards für erzeugten Strom durchgeführt. Es zeigt sich, dass die Qualität der elektrischen Energie mit abnehmender erzeugter Leistung abnimmt und möglicherweise nicht den Anforderungen der Norm entspricht. Es wird ein Algorithmus zur frequenzadaptiven Pulsweitenmodulation vorgeschlagen. Dieser ermöglicht es, die Qualität des von netzgekoppelten Spannungswechselrichtern eines Solarkraftwerks erzeugten Stroms in das Stromnetz zu verbessern.
Keywords: solar power plant; grid voltage inverter; power quality; higher harmonics; solarkraftwerk; netzspannungswechselrichter; stromqualität; höhere oberschwingungsströme